A CONVERGENCE OF GENRES: GOTHIC AND SCIENCE FICTION IN FRANKENSTEIN - Bernardo Pereira, Ismael (REVISTA DE LETRAS - JUÇARA, 2018)
This article aims to analyze the novel Frankenstein, by Mary W. Shelley, from a perspective of literary genres. The work is believed to manifest both traits of the Gothic genre––due to its structure and common themes to the period it was published––and of what would in future be called the Science fiction genre. Those elements are here observed, in the novel as well as in the context of its creation. In this sense, there is a convergence of genres taking place, albeit one of them is in its nascent form: Shelley's novel antecipate a scientific interest that would be specified in later fiction, being derived from her legacy. Tzvetan Todorov's perspective is considered, inasmuch as he defends the presence of multiple genres inside a work of fiction, as well as the creation of new literary genres from other, pre-existent, ones. It is concluded that the novel manifests enough elements to comprise both the genres here discussed, with its common and different traits.